Nanosponge as a novel delivery modulator of retinoic acid - Syed Omar, Sharifah Shakirah; Ab. Hadi, Hazrina; Doolanea, Abd Monem; Zulkifli, Nuraqilah (Mahidol University - Faculty of Pharmacy, 2024)
Retinoic acid is a derivative of vitamin A known for its use in the management of acne. The major limitations of retinoic acid application are its low solubility and instability in water, light, and heat. It also causes irritating side effects on the skin when used topically. In the current work, we demonstrated the entrapment of retinoic acid into nanosponge to improve the solubility and delivery of retinoic acid for skin application. The entrapment of retinoic acid into nanosponge wasinvestigated by varying polymer: crosslinker ratio, duration of homogenization, and drug: nanosponge ratio. High entrapment efficiency was achieved with nanosponge at 73.90%. The entrapment was confirmed through several characterizations including Attenuated Total Reflection Fourier Transform Infrared (ATR-FTIR), Differential Scanning Calorimetry (DSC), and Field Emission Scanning Electron Microscopy (FESEM). Higher solubilization was achieved with retinoic acid-loaded nanosponge compared to free drug. Franz cell studies show that the entrapment of retinoic acid in nanosponge slowed the release of retinoic acid and allowed it to remain within the skin layers longer.